Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ Ð´ÐµÐ½ÐµÑ€Ð²Ð°Ñ†Ð¸Ð¸ Ð¿ÐµÑ‡ÐµÐ½Ð¾Ñ‡Ð½Ð¾Ð¹ Ð°Ñ€Ñ‚ÐµÑ€Ð¸Ð¸ Ð¸ ÐºÑ€Ð¸Ð¾Ð´ÐµÑÑ‚Ñ€ÑƒÐºÑ†Ð¸Ð¸ Ð¿ÐµÑ‡ÐµÐ½Ð¸ Ð½Ð° Ð±Ð¸Ð¾Ñ…Ð¸Ð¼Ð¸Ñ‡ÐµÑÐºÐ¸Ðµ Ð¿Ð¾ÐºÐ°Ð·Ð°Ñ‚ÐµÐ»Ð¸ Ð¿Ñ€Ð¸ ÑÐºÑÐ¿ÐµÑ€Ð¸Ð¼ÐµÐ½Ñ‚Ð°Ð»ÑŒÐ½Ð¾Ð¼ Ñ†Ð¸Ñ€Ñ€Ð¾Ð·Ðµ - Chizh, N. A.; Belochkina, I. V.; Sandomirsky, B. P. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2007)
Efficiency of periarterial hepatic denervation and local cryodestruction of 10% liver mass was compared in the model of CCl4-induced diffusive rat liver injury. Hepatic artery was mechanically and surgically denervated. Results of blood serum biochemical studies (albumin, alanine-aminotransferase, aspartate-aminotransferase, thymol test) have demonstrated that all types of surgery contribute equally to an accelerated normalisation of studied biochemical indices within 2 observation months. A technical simplicity of hepatic artery cryodestruction performance is noted as this denervation method advantage.